Sensitivity of Pressure-Mediated Reflection Spectroscopy to Detect Dose-Dependent Changes in Skin Carotenoids: A Randomized Controlled Trial. (14th June 2022) - Casperson, Shanon; Roemminch, James; Hess, Julie; Larson, Kate; Palmer, Daniel; Jahns, Lisa
Abstract: Objectives: Skin carotenoids respond to changes in the consumption of carotenoid-rich fruits and vegetables (FV); however, the sensitivity of pressure-mediated reflection spectroscopy (PMRS) to detect changes in skin carotenoids in response to changes in FV consumption is not yet known. The objective of this study was to assess the sensitivity of PMRS to detect dose-dependent increases in skin carotenoids. Methods: In this 8-week parallel controlled trial, participants were randomly assigned to either a control group (water; n = 19; age: 31 ± 14; BMI: 26 ± 3) or to one of three high-lycopene vegetable juice consumption doses – 1) the LOW group consumed 5.5 fl. oz./day (0.8 cups or 1.5 servings; n = 22; age: 33 ± 14; BMI: 25 ± 3); 2) the MED group consumed 10 fl. oz./day (1.5 cups or 3 servings; n = 21; age: 30 ± 8; BMI: 26 ± 2); 3) the HIGH group consumed 13 fl. oz./day (2.0 cups or 4 servings; n = 17; age: 35 ± 14; BMI: 24 ± 3). All beverages were provided in premeasured containers for daily consumption. PMRS-assessed skin carotenoids were measured weekly in triplicate. The mean PMRS intensity of the three scans was used for the analyses. Results: PMRS-assessed skin carotenoids were greater than baseline starting at week 2 in the HIGH group (p ≤ .003), week 4 in the MED group (p ≤ .002), and week 5 in the LOW group (p ≤ .04). No changes were observed in the control group. Differences in PMRS-assessed skin carotenoids were observed beginning at week 2 between the control and HIGH groups (p ≤ .04), at week 4 between the LOW and HIGH groups (p ≤ .05), and at week 8 between the control and MED groups (p = .01). No differences were observed between the LOW and MED groups, the MED and HIGH groups, or the control and LOW groups. Conclusions: In conclusion, PMRS-assessed skin carotenoids increase in a linear dose- and time-dependent manner. These preliminary results indicate that PMRS is capable of detecting changes in skin carotenoids when the daily consumption of carotenoid rich FV are increased by at least 0.8 cups or 1.5 servings for a minimum of 5 weeks. These preliminary results also indicate that the lowest level of detection between groups is the consumption of 1.5 cups or 3 servings of carotenoid rich FV daily for a minimum of 8 weeks. Changes in consumption levels or differences between groups below these thresholds may not be detected using PMRS. Funding Sources: Study was supported by USDA ARS.